PERILAKU KONSUMEN DAN FAKTOR YANG MEMPENGARUHI CUSTOMER LOYALTY PADA PERUSAHAAN RETAIL - hasan, golan (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
As overall service quality is a marketing strategy which used to maintain the relationship between costumers and a company, it needs to be nurtured properly. Good service from a company has long-term benefits which provide positive impacts in the form of corporate profits for facing the competition. By doing so, a company needs to improve overall service quality in order to build relationship strength and relationship quality due to the good relationship to its costumers, Â which in turn, will leads to customer loyalty.This study aimed to test whether there were some impacts between the overall service quality, relationship strength and relationship quality on customer loyalty in some retail companies. The sample was the customers of some department stores (Top 100, JC Supermarket, Golden Truly and Hypermart) in Batam. This study was tested on a sample of 116 respondents. The method was a survey via distributing questionnaires to the sample and using regression analysis instrument.This study revealed that overall service quality and relationship strength significantly have a positive impact on customer loyalty. However, the relationship quality did not have a significant impact on customer loyalty